Effect of different dietary inclusion levels of whole plant green tomato (Physalis philadelphica) silage on nutrient intake and digestibility, and in vitro rumen fermentation kinetics in sheep - Robles-Jimenez, Lizbeth E.; Narváez-López, Alondra C.; Chay-Canul, Alfonso J.; Sainz-Ramirez, Aurora; Castelan-Ortega, Octavio A.; Zhang, Naifeng; Gonzalez-Ronquillo, Manuel; Vargas-Bello-Pérez, Einar (Frontiers in Veterinary Science, 2022)
Mexico has many agricultural by-products that can be used for animal feed, and green tomatoes are produced throughout the country and can be an alternative to overcome the high prices of cereal-based feeds. This study determined in vitro fermentation kinetics, production performance, nutrient intake, digestibility, and nitrogen balance from sheep supplemented with whole plant green tomato (GT) on corn silage (CS) based diets. For 21 days, eighteen Suffolk lambs (38 ± 4 kg of live weight) were grouped into three dietary GT inclusion levels to replace CS: a control diet based on 100% CS (GT0, 570 g /kg dry matter, DM), while 100 g/kg DM (GT100) and 200 g/kg DM (GT200) of GT were included as a replacement for CS. A completely randomized design was used to measure in vitro gas production, in vitro rumen fermentation, chemical composition, and in vivo parameters. In vitro gas production, “A” (ml/g DM), fermentation rates “B,” (h−1), and “C” (h−½), were lower for GT200, while DM disappearance (mg/100mg) was lower for GT100 compared with GT0. Compared to GT0, GT100 and GT200 did not affect (P > 0.05) DM and organic matter (OM) intake (g/kgLW0.75). Ether extract intake was higher for GT0 and GT100 (P < 0.001) compared to GT200. Neutral detergent fiber (NDF) intake was higher (P < 0.05) for GT200 compared with GT0. Intake of lignin was higher (P < 0.001) for GT200 than that of GT0 and GT100. Digestibility coefficients for DM, OM, NDF, and Acid detergent fiber (ADF) were lower (P < 0.05) in GT100 than in the rest of the treatments. Nitrogen intake and N excreted in feces and urine were lower (P < 0.001) for GT0. N balance was negative for all treatments, being higher for GT200 (P < 0.05). Overall, the addition of GT at 100 or 200 g/kg DM in sheep diets negatively affects nutrient digestibility and N balance, so their dietary inclusion is not recommended.